Peningkatan Pemahaman Literasi Bahasa Inggris dengan Model Small Group Discussion Berbantuan Komik Digital - Bhuana Dewati (Neolectura, 2021)
Literacy skills in reading English need to be mastered by junior high school students. However, the reality in Junior High School N 1 Wanadadi obtained many students who still can not read English. This indicates that his literacy ability is still low. Therefore, an innovation in English learning is needed by supporting technological developments. One of them is by learning Small Group Discussion assisted by digital comics. This study is a Class Action Research with two silus, and each cycle consists of three meetings. Classroom action research procedures in the form of planning, implementation, observation, and reflection. The data analysis technique used is descriptive analysis. The research subjects of students of class VIIID of SMP Negeri 1 Wanadadi semester 1 amounted to 30 students. The data collection techniques are observations, interviews, and tests. The results showed that the use of a Small Group Discussion model assisted by digital comics can improve English literacy skills. Students look actively studying in the classroom and can learn independently.